The illusion of accountability in the European Union (Taylor & Francis, 2009)
This book examines accountability in the EU from different perspectives and considers whether EU citizens have real opportunities for holding decision-makers accountable. This book critically analyses five arguments which claim there are sufficient means for holding decision-makers to account in the Union.
FP7 Ideas: European Research Council
English
Keywords: Politics & government; accountibility; european union